In envy country stories - Frank, Joan, 1949- (Richard Sullivan prize in short fiction., 2010)
"Set in Paris, California, Italy, and Spain, Joan Frank's second story collection explores the uncertainties and triumphs of women and men in and out of love and marriage at varying ages and stages of contemporary American Life"--Cover p.[4].